(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Currently, the concept of subject is being submitted to a series of refutations and reformulations. Among them, the reconsideration of the convergent processes in its constitution can contribute to clarify the statute and the reach of the contemporary concept of subjectivity. Starting from a comparative reading of Freud and Lévinas, the de-centering of the subject and its founding dis-encounter with the Other is discussed, whereas also the consequences for the self comprehension (Selbstverständnis) of the subject and its relation towards language are analyzed.